Crioconservación De Semen En Perros Domésticos (Canis Lupus Familiaris), En La Clínica Animal Kingdom - Acurio Aguiar, Adriana Gabriela (2019)
Determining the microscopic characteristics of cryopreserved canine semen at different evaluation times was the main objective of this research, through the fundamental parameters of sperm samples motility and vitality that determine from cryopreserved semen viability, thus proposing to implement other reproduction techniques in order to provide animal welfare and prevent the spread of sexual diseases to pets. The samples they will use were collected by the manual extraction method of 5 canine males of the Schnauzer, Miniature breed between 2.5 and 3 years old, after the corresponding analysis, three straws of each specimen were prepared, which were stored at a temperature of -196 ° C in liquid nitrogen in times of 15, 30 and 45 days of freezing respectively. The data obtained from each of the samples made were evaluated, processed and analyzed. An average of 87.2% sperm motility was obtained at 15 days post freezing, 86.4% sperm motility at 30 days post freezing and 86.2% sperm motility at 45 days post freezing; and a sperm vitality of 83.8% at 15 days post freezing, sperm vitality of 83% at 30 days post freezing and a sperm vitality of 83% at 45 days post freezing, indicating defrosting at 15 days as the best result, being acceptable values as far as semen quality is concerned. The results obtained in this research updated information to initiate future research, evidencing the results obtained and thus contributing knowledge to the development of biotechnology techniques of canine reproduction in Ecuador